2013
DOI: 10.4236/ojem.2013.12003
|View full text |Cite
|
Sign up to set email alerts
|

Tako-tsubo syndrome after administration of intravenous adrenaline during atrioventricular block

Abstract: We describe the clinical case of a 70-year-old woman with complete atrioventricular block that after administration of intravenous adrenaline, developed electrocardiographic changes suggestive of acute coronary syndrome, together with apical dyskinesia of the left ventricle. After ruling out the existence of coronary lesions, and after total recovery of the echocardiographic alterations in segmental contractility, she was diagnosed as Tako-tsubo syndrome induced by administration of adrenaline. This is the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In our case, it is possible that the administration of epinephrine during the brief cardiac arrest may have contributed to the development of TTC as this mechanism has been previously suggested. 9 The correct management of TTC with complete AV block is uncertain and can be challenging. Literature on this subject is limited but recent studies have suggested that AV block persists despite resolution of the cardiomyopathy, and that permanent pacemaker implantation improves mortality in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…In our case, it is possible that the administration of epinephrine during the brief cardiac arrest may have contributed to the development of TTC as this mechanism has been previously suggested. 9 The correct management of TTC with complete AV block is uncertain and can be challenging. Literature on this subject is limited but recent studies have suggested that AV block persists despite resolution of the cardiomyopathy, and that permanent pacemaker implantation improves mortality in these patients.…”
Section: Discussionmentioning
confidence: 99%